A multidisciplinary pulmonary embolism response team (PERT)—experience from a national multicenter consortium. (August 2019) - Schultz, Jacob; Giordano, Nicholas; Zheng, Hui; Parry, Blair A.; Barnes, Geoffrey D.; Heresi, Gustavo A.; Jaber, Wissam; Wood, Todd; Todoran, Thomas; Courtney, D. Mark; Naydenov, Soophia; Khandhar, Sameer; et al.
Background: We provide the first multicenter analysis of patients cared for by eight Pulmonary Embolism Response Teams (PERTs) in the United States (US); describing the frequency of team activation, patient characteristics, pulmonary embolism (PE) severity, treatments delivered, and outcomes. Methods: We enrolled patients from the National PERT Consortium™ multicenter registry with a PERT activation between 18 October 2016 and 17 October 2017. Data are presented combined and by PERT institution. Differences between institutions were analyzed using chi-squared test or Fisher's exact test for categorical variables, and ANOVA or Kruskal-Wallis test for continuous variables, with a two-sided P value < 0.05 considered statistically significant. Results: There were 475 unique PERT activations across the Consortium, with acute PE confirmed in 416 (88%). The number of activations at each institution ranged from 3 to 13 activations/month/1000 beds with the majority originating from the emergency department (281/475; 59.3%). The largest percentage of patients were at intermediate–low (141/416, 34%) and intermediate–high (146/416, 35%) risk of early mortality, while fewer were at high-risk (51/416, 12%) and low-risk (78/416, 19%). The distribution of risk groups varied significantly between institutions ( P  = 0.002). Anticoagulation alone was the most common therapy, delivered to 289/416 (70%) patients with confirmed PE. The proportion of patients receiving any advanced therapy varied between institutions ( P  = 0.0003), ranging from 16% to 46%. The 30-day mortality was 16% (53/338), ranging from 9% to 44%. Conclusions: The frequency of team activation, PE severity, treatments delivered, and 30-day mortality varies between US PERTs. Further research should investigate the sources of this variability.